Information Communication Technologies 2008
DOI: 10.4018/978-1-59904-949-6.ch089
|View full text |Cite
|
Sign up to set email alerts
|

ICT-Enabled Education in Africa

Abstract: This essay prompts critical thinking on the way ICT-enabled education programs in Africa have been conceptualized and implemented. It reflects mainly on the experiences of the African SchoolNet movement over the past decade. It highlights important lessons and demonstrates the beneficial effects of technology-enhanced learning programs on African learners and teachers who have had the privilege of being included in SchoolNet initiatives. However, it also shows that the accumulated interventions and programs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Furthermore, it is left to observe how South Africa's educational sector navigates around the somewhat unimplemented national policy framework on how to integrate technological convergence and advancements into tangible and best practices for the educational sector. With the uncertainty of the COVID-19 pandemic, there is the need for revisiting these policies (Council on Higher Education 2000;Department of Education 2004;Isaacs 2007;National Working Group 2002), and frameworks on proper utilisation of online systems to continue the seamless transition from campus-based approaches to virtual nationwide. As stated in the White Paper on e-Education of August 2004, implementation of policies around e-teaching and learning must 'transcend the mere exchange of information and [be] transform[ed] into a range of [creative and inclusive] learning activities that meet educational objectives [to ensure] the meaningful interaction of students with information' in South Africa (Department of Education 2004:14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is left to observe how South Africa's educational sector navigates around the somewhat unimplemented national policy framework on how to integrate technological convergence and advancements into tangible and best practices for the educational sector. With the uncertainty of the COVID-19 pandemic, there is the need for revisiting these policies (Council on Higher Education 2000;Department of Education 2004;Isaacs 2007;National Working Group 2002), and frameworks on proper utilisation of online systems to continue the seamless transition from campus-based approaches to virtual nationwide. As stated in the White Paper on e-Education of August 2004, implementation of policies around e-teaching and learning must 'transcend the mere exchange of information and [be] transform[ed] into a range of [creative and inclusive] learning activities that meet educational objectives [to ensure] the meaningful interaction of students with information' in South Africa (Department of Education 2004:14).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have argued that the use of e-teaching and learning is advantageous to the development of cultural, critical and operational skills for both students and facilitators (Azeez & Van Der Vyver 2018;Isaacs 2007;Kaliisa & Picard 2017;Mayisela 2013;Mpungose 2020b;Msomi & Bansilal 2018;Zimba et al 2020). Facilitators are also expected to be equipped with the knowledge about internet-mediated academic encounters seeing they are vital to achieving maximum success for e-teaching and learning in South Africa (Motala & Menon 2020).…”
Section: Assessing the Practicality And Implications Of Online Pedagogymentioning
confidence: 99%
“…South Africa has continued to champion massive deployment of online learning tools via network technologies throughout the academic institutions, especially the tertiary institutions (Isaacs, 2007). Hence, tools to access online resources such as computers like desktops, laptops and smartphones are being deployed for educational purposes in South Africa tertiary institutions (Aheto, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2015, 57 million South African children of primary school age were still out of school (UNESCO, 2015), and South African primary schools were placed 132 out of 144 countries with regard to quality teaching (World Economic Forum [WEF], 2013). Although it has been reported that only 6% of classrooms have computers connected to the Internet (Isaacs, 2007), access to the Internet via mobile phones is significantly higher and Wikipedia is the sixth most visited website in the country (Alexa, 2017). All but one of South Africa’s eleven official languages has a Wikipedia edition, 2 and a number of projects initiated by volunteers and supported by Wikimedia Chapters and User Groups have been developed to make Wikipedia accessible offline.…”
Section: The Casementioning
confidence: 99%